IMPLEMENTASI KEBIJAKAN KETENAGAKERJAAN DI KABUPATEN BEKASI - Richi Agung Ervanto; Irwan Tahir; Rossy Lambelanova (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
The theory used as an analytical knife in writing this thesis is the theory of policy implementation model according to Muchlis Hamdi (2014) which explains the description of the dynamics of the movement of policy implementation, namely the dimensions of productivity, linearity and efficiency and the factors that can affect the success of policy implementation, namely the determinants of policy substance, implementing task behavior, network interaction, target group participation and resources. The method used is a qualitative approach, data collection techniques are interviews, document review, and analysis. Based on the description obtained that the implementation of employment policies in Bekasi Regency has not run optimally, productivity has not reached the target, both the target for reducing the open unemployment rate and the target for minimum service standards for manpower placement. The service linearity between job seekers registration and job vacancies registration is in accordance with predetermined procedures, time, cost, place and implementer, but in terms of service to employers, procedures for placement of workers and follow-up to the appointment of prospective job seekers, the Bekasi Regency Manpower Office does not yet have a written standard operating procedure (SOP), so it cannot be explained whether the service is in accordance with the standard specification guidelines that have been determined. the efficiency of inter-work services is quite efficient, but inter-work services are still done manually and have not used online-based technology that can expand the range of services.